A novel bioactive edible coating based on sodium alginate and galbanum gum incorporated with essential oil of Ziziphora persica: The antioxidant and antimicrobial activity, and application in food model. (November 2017) - Hamedi, Hassan; Kargozari, Mina; Shotorbani, Peyman Mahasti; Mogadam, Nima Babolani; Fahimdanesh, Maryam
Abstract: Galbanum, an aromatic oleo-resin gum, is produced from umbelliferous Persian plant species in the genus Ferula with the common Persian name "Barije", chiefly endemic flora of the mountain ranges of northern Iran. Ziziphora persica is an edible medicinal plant, which is widely distributed in Iran, Turkey and Eurasian countries. The aims of the present research were to produce novel bioactive edible coatings based on sodium alginate (Alg), galbanum oleo-resin gum (GG) and the biocomposite of alginate and galbanum (CAG) containing different concentration of Ziziphora essential oil (ZEO), and evaluate the antioxidant and the antimicrobial activities of these substances in vitro and their effect on the quality and shelf life of chicken fillet during cold storage. Overall, the MIC and MBC values of GG and ZEO extracts ranging from 1.25 to 50 (μg mL −1 ) proved that gram-positive bacteria were more susceptible to GG and ZEO than gram-negative bacteria. The high phenolic and flavonoid contents and antioxidant activities of GG and ZEO were proved by in vitro analysis. Results showed that coatings of Alg had no significant effect on decreasing the microbial load of aerobic mesophilic and psychrotrophic bacteria, lactic acid bacteria, Pseudomonas spp., and Enterobacteriaceae, as well as L. monocytogenes (p > 0.05), while the coating of fillet with GG, CAG alone and in combination with ZEO showed a significant differences with the other treatments during 12 days of storage (p < 0.05). The results also showed that TVBN, TBARS and peroxide formation in the samples treated by GG/ZEO was significantly lower than other groups (p < 0.05). Graphical abstract: Highlights: New bioactive edible composite coating of sodium alginate and F. gummosa galbanum gum incorporated with Z. persica essential oil was developed. The alginate, galbanum gum, and their composite can be used as bioactive edible coatings for preservation and shelf-life extension of foods. Ziziphora persica can be used as a potential food preservative and a natural flavorant. The chicken fillets coated with Alg, GG, and CAG incorporated with ZEO had better microbiological and chemical quality than uncoated samples.